1992
DOI: 10.1152/jappl.1992.72.5.1868
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary angiotensin-converting enzyme substrate hydrolysis during exercise

Abstract: We examined exercise-induced changes in indicator-dilution estimates of the angiotensin-converting enzyme first-order kinetic parameter, the ratio of a normalized maximal enzymatic conversion rate to the Michaelis constant (Amax/Km), which, under stable enzymatic conditions, will vary with the pulmonary vascular surface area accessible to vascular substrate, the extravascular lung water (an index of the proportion of lung tissue perfused), and the central blood volume (from pulmonary trunk to aorta). Experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0
2

Year Published

1992
1992
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 0 publications
2
8
0
2
Order By: Relevance
“…The line for the control group was quite close to the line of identity. This line is similar to those generated in animal models (22,27) and is likely representative of the true surface area-flow relationship in healthy human subjects under physiologic resting conditions. The line for the IPAH group was nearly parallel to the line for the controls, suggesting that although the lungs of patients with IPAH are operating with a reduced number of perfused functional capillaries, this number would be close to the number of capillaries that would be perfused in a healthy lung under low flow states.…”
Section: Discussionsupporting
confidence: 77%
“…The line for the control group was quite close to the line of identity. This line is similar to those generated in animal models (22,27) and is likely representative of the true surface area-flow relationship in healthy human subjects under physiologic resting conditions. The line for the IPAH group was nearly parallel to the line for the controls, suggesting that although the lungs of patients with IPAH are operating with a reduced number of perfused functional capillaries, this number would be close to the number of capillaries that would be perfused in a healthy lung under low flow states.…”
Section: Discussionsupporting
confidence: 77%
“…24 It has been suggested that A max /K m cannot be used as a quantitative index of perfused capillary surface area because of the presence of the nonreactive cis isomer BPAP fraction. 15,25 This fraction was estimated to be Ϸ15% in buffer solution, 26 whereas in vivo it appears to represent 7% of all BPAP, 13 probably because of the presence of natural isomerases in plasma. However, studies done with different substrates concurrently injected, or correcting for the nonreactive fraction, confirm that A max /K m is a quantifiable index of perfused lung capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…PCEB-ACE dysfunction has been an early and sensitive finding in animal models of lung injury, 8,9 and, under physiological conditions, PCEB-ACE assays estimate enzyme mass 5 and perfused vascular surface area. 7,15 Although ACE is present on all endothelial cells, microvessels, principally capillaries, are responsible for the great majority of single-pass transpulmonary hydrolysis, 9 whereas the contribution of plasma ACE is minimal. 9 Thus in our studies, measurement of pulmonary ACE activity represents in practical terms PCEB-ACE activity.…”
Section: Discussionmentioning
confidence: 99%
“…Now assume that the tracer oxygen undergoes instantaneous equilibrium partition between RBCs, plasma, Disse space and hepatocytes at each point along the length (that is, y = h p ; u = u; and z = Ahpu; where Ac, is the ratio of erythrocyte/plasma oxygen concentration and hh is the ratio of hepatocyte/plasma oxygen concentrafion, as indicated by our qualitative analysis of the data. The solution to equation 5 for an impulse input is, as described previously (5, 8, 16), where qo is the amount of tracer injected, Fb is sinusoidal blood flow, kses is the form of the rate constant which appears in the integrated equation, (20). Equation 6 can be viewed as an analog of the Crone expression (211, in which sequestration takes the place of the permeability surface area product.…”
Section: It Can Be Shownmentioning
confidence: 99%